Resistance of Cucurbita spp. germplasm to the fungus Macrophomina phaseolina - Lima, Fernanda; Barboza, Michele; Ambrósio, Márcia; Albuquerque, Neilza; Nunes, Glauber; Barros Júnior, Aurélio; Nogueira, Geovane; Silveira, Lindomar (Revista Ciência Agronômica, 2021)
The objective of this study was to evaluate genotypes of Cucurbita moschata and Cucurbita maxima for resistance to the fungus Macrophomina phaseolina (Taissi) Goid. The experiment used 17 accessions of Cucurbita moschata Duchesne (ABTOU 805 F1, ABO 168, ABPUN 206 F4, ABPUN 201 F6, ABTOU 805 F4, ABPUN 206 F6, ABPUN 206 F2, ABPUN 206 F1, ROÇA DE PAI, ABTOU 805 F4, P114-1, P160-2, P11-2, P114-6, P131-21, P114-02 and P97-1), 20 accessions of Cucurbita maxima Duchesne (ABPUN-213, ABCRN-304, ABTOU-802-F4, ABAPO-002, ABAPO-005, JCCM-2014, ABO-156, ABPUN-212, ABCRN-315, ABTOU-802 F1, ABAPO-007, JERIMUM LU, ABAPO-024, ABPUN-211, RGV 2011.1 01, ABCRN-306, ABBAR-101, ABCRN-302, ABTOU-802 F3 and JCCA) preserved in the Cucurbit Germplasm Collection of the Federal Rural University of the Semi-Arid Region (UFERSA). Four commercial controls were also used, two for each species. In both studies, three isolates of M. phaseolina were inoculated, which are kept at the Fungal Culture Collection of UFERSA: MM1531 (GenBank: MN136199), ME249 and ME250. Plants received inoculum of the pathogen in pieces of colonized toothpick and were evaluated for incidence and severity of the disease. Both species showed resistant plants, but with varied frequencies for the accessions. Considering the species, the frequencies observed for C. moschata were higher than those observed for C. maxima.